JCU 2017 Reviewers (Journal of Clinical Ultrasound, 2018)
Ovarian fibrothecomas are important from an imaging standpoint because they appear as solid masses, thereby mimicking subserosal fibroids or malignant ovarian neoplasms. They are usually seen in post-menopausal women. We present a case of a 25-year-old nulli-gravida presenting with 8 months of secondary amenorrhea, in whom ultrasonography revealed a multi-loculated solid cystic lesion with a central solid component showing moderate internal vascularity. MRI pelvis revealed a lesion abutting the right ovary with peripheral cysts. Ovarian-sparing cystectomy was performed which led to resolution of amenorrhea. Histopathology revealed the resected specimen to be ovarian fibrothecoma with predominance of thecoma component. The solid cystic nature of the lesion and its presentation at a young age highlight the rarity of our case and the presence of the recently described "peripheral cyst sign" adds to the teaching points.